The Resonance of Unseen Things : Poetics, Power, Captivity, and UFOs in the American Uncanny - Lepselter, Susan Claudia (Book collections on Project MUSE., 2016)
"The Resonance of Unseen Things offers an ethnographic meditation on the "uncanny" persistence and cultural freight of conspiracy theory. The project is a reading of conspiracy theory as an index of a certain strain of late 20th-century American despondency and malaise, especially as understood by people experiencing downward social mobility. Written by a cultural anthropologist with a literary background, this deeply interdisciplinary book focuses on the enduring American preoccupation with captivity in a rapidly transforming world. Captivity is a trope that appears in both ordinary and fantastic iterations here, and Susan Lepselter shows how multiple troubled histories--of race, class, gender, and power--become compressed into stories of uncanny memory"--Publisher's description